The Gofman-Tamplin Cancer Risk Controversy and Its Impact on the Creation of BEIR I and the Acceptance of LNT - Calabrese, Edward (La Medicina del Lavoro, 2023)
Background: The major public dispute between John Gofman and his colleague Arthur Tamplin and the United States (US) Atomic Energy Commission (AEC) at the end of the 1960s and during the early 1970s significantly impacted the course of cancer risk assessment in the US and worldwide. The challenging and provocative testimony of Gofman to the US Senate in early 1970 lead to the formation of the US National Academy of Sciences (NAS) Biological Effects of Ionizing Radiation (BEIR) I Committee in order to evaluate the accuracy of claims by Gofman and Tamplin that emissions from nuclear power plants would significantly increase the occurrence of genetic defects and cancers. BEIR I recommended the adoption of the linear non-threshold (LNT) dose response model for the assessment of cancer risks from radiation exposures. The US EPA adopted this recommendation and generalized it to incorporate chemical carcinogens, thereby affecting cancer risk assessments over the next decades. Despite the scientific limitations and ideological framework of their perspectives, Gofman and Tamplin are of considerable historical importance since they had essential roles in affecting the adoption of LNT by regulatory agencies.